Neuroprotective effects of methanolic extract from Chuanxiong Rhizoma in mice with middle cerebral artery occlusion-induced ischemic stroke: suppression of astrocyte- and microglia-related inflammatory response - Chiyeon Lim; Sehyun Lim; So-Jung Moon; Suin Cho (BMC, 2024)
Abstract Background In traditional Asian medicine, dried rhizomes of Ligusticum chuanxiong Hort. (Chuanxiong Rhizoma [CR]) have long been used to treat pain disorders that affect the head and face such as headaches. Furthermore, they have been used primarily for blood circulation improvement or as an analgesic and anti-inflammatory medicine. This study aimed to investigate the neuroprotective effects of a methanol extract of CR (CRex) on ischemic stroke in mice caused by middle cerebral artery occlusion (MCAO). Methods C57BL/6 mice were given a 1.5-h transient MCAO (MCAO control and CRex groups); CRex was administered in the mice of the CRex group at 1,000-3,000 mg/kg either once (single dose) or twice (twice dose) before MCAO. The mechanism behind the neuroprotective effects of CRex was examined using the following techniques: brain infarction volume, edema, neurological deficit, novel object recognition test (NORT), forepaw grip strength, and immuno-fluorescence staining. Results Pretreating the mice with CRex once at 1,000 or 3,000 mg/kg and twice at 1,000 mg/kg 1 h before MCAO, brought about a significantly decrease in the infarction volumes. Furthermore, pretreating mice with CRex once at 3,000 mg/kg 1 h before MCAO significantly suppressed the reduction of forepaw grip strength of MCAO-induced mice. In the MCAO-induced group, preadministration of CRex inhibited the reduction in the discrimination ratio brought on by MCAO in a similar manner. CRex exhibited these effects by suppressing the activation of astrocytes and microglia, which regulated the inflammatory response. Conclusions This study proposes a novel development for the treatment of ischemic stroke and provides evidence favoring the use of L. chuanxiong rhizomes against ischemic stroke.